2019
DOI: 10.1093/ntr/ntz056
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Reward-Enhancing Effects of Nicotine on Ethanol Reinforcement: A Reinforcer Demand Analysis

Abstract: Background Alcohol is often consumed with tobacco, and dependence to alcohol and tobacco are highly comorbid. In addition, there are differences in the prevalence of nicotine- and alcohol-abuse between the sexes. Nicotine produces enhancing effects on the value of other reinforcers, which may extend to alcohol. Methods Male and female Wistar rats were trained to self-administer 15% ethanol solution in 30-minute sessions. Once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…It is important to point out that there was a significant difference in the effect of contingent "lowcost" and contingent "high-cost" nicotine availability on the responding for ethanol because only when nicotine was available on the FR1 schedule of reinforcement the consumption of the ethanol increased (see Figure 5A). Overall, these findings support a body of literature showing that nicotine increases the reinforcing value of ethanol (Barrett et al, 2020;Doyon et al, 2013;Lallemand et al, 2007;Lárraga et al, 2017;Marshall et al, 2003;Smith et al, 1999) with additional refinement of our understanding of roles of nicotine contingency and "cost" in the interaction effects with ethanol. Our interaction tests also showed that contingent "low-cost" ethanol significantly decreased responding for nicotine on a progressive schedule of reinforcement while noncontingent nicotine or continent "high-cost" nicotine availability had no effect (Figure 5B).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is important to point out that there was a significant difference in the effect of contingent "lowcost" and contingent "high-cost" nicotine availability on the responding for ethanol because only when nicotine was available on the FR1 schedule of reinforcement the consumption of the ethanol increased (see Figure 5A). Overall, these findings support a body of literature showing that nicotine increases the reinforcing value of ethanol (Barrett et al, 2020;Doyon et al, 2013;Lallemand et al, 2007;Lárraga et al, 2017;Marshall et al, 2003;Smith et al, 1999) with additional refinement of our understanding of roles of nicotine contingency and "cost" in the interaction effects with ethanol. Our interaction tests also showed that contingent "low-cost" ethanol significantly decreased responding for nicotine on a progressive schedule of reinforcement while noncontingent nicotine or continent "high-cost" nicotine availability had no effect (Figure 5B).…”
Section: Discussionsupporting
confidence: 84%
“…Some of the variability in the preclinical studies likely stems from variability in methodological approaches to sample relevant data. For example, some studies rely on noncontingent (bottle or vapor) ethanol delivery (Chandler et al, 2020; Lallemand et al, 2007; Marshall et al, 2003; Potthoff et al, 1983; Smith et al, 1999), while others utilize contingent operant protocols for ethanol self-administration (Barrett et al, 2020; Deehan et al, 2015; Doyon et al, 2013; Lárraga et al, 2017). Likewise, nicotine administration in those previous studies also varied with nicotine consumed noncontingently through drinking solutions (Lallemand et al, 2007; Marshall et al, 2003; Potthoff et al, 1983), contingently through drinking solutions (Deehan et al, 2015), noncontingently using systemic injections (Barrett et al, 2020; Doyon et al, 2013; Smith et al, 1999), or contingently using intravenous self-administration protocols (Chandler et al, 2020; Lárraga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A higher reward responsiveness of males than females is known. This is also related to the higher impulsivity [ 127 , 128 , 129 , 130 , 131 ], reward dependence [ 16 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ], and novelty seeking [ 140 , 141 , 142 , 143 ] of males than females. The result is a higher risk taking of males than females [ 127 , 144 , 145 , 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent report used a reinforcer demand analysis in which Wistar rats that were trained to self-administer alcohol were first pretreated with nicotine followed by an exponential reinforcer demand method to measure the reinforcement index of alcohol following nicotine treatment. In this study, male rats displayed higher alcohol reinforcement at baseline, whereas low-to-moderate doses of nicotine increased perseverative responding for alcohol infusions only in females ( Barrett et al, 2020 ). These data suggest that female rodents may exhibit unique behavioral responses to co-consumption of alcohol and nicotine, which could have important consequences for treating comorbid alcohol and nicotine use disorders.…”
Section: Sex Differences In Alcohol and Nicotine Co-consumptionmentioning
confidence: 52%
“…While the comorbidity of alcohol and nicotine use disorders has been widely studied in human patients, less research has been Barrett et al, 2020 bPiDi, N,N-decane-1,10-diyl-bis-3-picolinium diiodide; CPP, conditioned place preference; DID, drinking-in-the-dark; KO, knockout; LORR, loss of righting reflex; n.d., no difference.…”
Section: Sex Differences In Alcohol and Nicotine Co-consumptionmentioning
confidence: 99%